Directly Diphenylborane‐Fused Porphyrins. (28th January 2016) - Fujimoto, Keisuke; Oh, Juwon; Yorimitsu, Hideki; Kim, Dongho; Osuka, Atsuhiro
Abstract: Mono‐ and bis(diphenylborane)‐fused porphyrins were synthesized from the corresponding β‐(2‐trimethylsilylphenyl)‐substituted porphyrins through the sequence of Si–B exchange reaction, intramolecular bora‐Friedel–Crafts reaction, and ring‐closing Si–B exchange reaction. Effective electronic interactions of the empty p‐orbital of the boron atom with the porphyrin π‐circuit lead to red‐shifted absorption spectra and substantially decreased LUMO energy levels. Pyridine adds at the boron center to cause disruption of the electronic interaction of the boron atom with large association constants (1.9–17×10 4  m −1 ) depending on the central metal at the porphyrin. The Zn II complex behaved as a hetero‐dinuclear Lewis acid, exhibiting regioselective binding of pyridines at the boron or the zinc center.